Surface-specific thermal spin-depolarization on the half-metallic Heusler films - Kazuki Sumida; Masaaki Kakoki; Yuya Sakuraba; Keisuke Masuda; Kazuki Goto; Takashi Kono; Koji Miyamoto; Yoshio Miura; Kazuhiro Hono; Taichi Okuda; Akio Kimura (Communications Physics)
Abstract Half-metallic ferromagnets exhibit a perfect spin-polarization at the Fermi energy. Among many candidates, Co2MnSi Heusler alloy is the most investigated material due to its half-metallic nature and high Curie temperature (T C). Magnetic junction devices using Co2MnSi show remarkable performance at low temperatures. However, the performance is significantly degraded at room temperature, which requires a detailed understanding of the temperature-dependent electronic structure of Co2MnSi films. Here, using surface-sensitive spin- and angle-resolved photoelectron spectroscopy combined with first-principles calculations, we verify the temperature- and momentum-dependent spin-polarization of Co2MnSi thin-film. The recorded spin-polarization reaches  ~ 60-75% at 50 K, while it reduces  ~ 30-50% at 300 K. The observed surface-specific spin-depolarization behavior can be described by the thermally excited magnon model even well below T C, and we conclude that the spin-fluctuation is markedly enhanced on its surface. Our findings provide insights into the temperature-dependent electronic structure of half-metallic Heusler films, which could have significant implications for future spintronic applications.